2017
DOI: 10.1002/jobm.201600755
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism ofTrichodermaisolates againstLeucoagaricus gongylophorus(Singer) Möller

Abstract: Filamentous fungi from the genus Trichoderma are commonly found in soil. They are considered facultative mycoparasites, and are antagonists of other fungi such as the cultivar of leaf-cutting ants (Leucoagaricus gongylophorus). The aim of the present study was to bioprospect Trichoderma spp. from different soils collected from Gurupi, Tocantins, Brazil, for antagonistic effects against the mutualistic fungus of leaf-cutting ants. To isolate filamentous fungi, samples were collected from six locations. Prelimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…Even if Trichoderma is not directly pathogenic to the ants, it could be used as an additional tool for ant control as it can act as an antagonist of the symbiotic fungus which the ants cultivate and feed on [36]. Notwithstanding the production of metabolites that adversely act on ant colonies.…”
Section: Effects Of Contact Between Ants and Fungal Sporesmentioning
confidence: 99%
“…Even if Trichoderma is not directly pathogenic to the ants, it could be used as an additional tool for ant control as it can act as an antagonist of the symbiotic fungus which the ants cultivate and feed on [36]. Notwithstanding the production of metabolites that adversely act on ant colonies.…”
Section: Effects Of Contact Between Ants and Fungal Sporesmentioning
confidence: 99%
“…However, these putative mechanisms seem not enough to outcompete Escovopsis growth, which was attracted to both fungal cultivars and inhibited their growth in the majority of FEI ( Figure 1 ). It is worthy to point that fungal cultivar inhibition is not an outcome particular to interactions with Escovopsis , as it also results from in vitro interactions between cultivar and other filamentous fungi ( Ortiz and Orduz, 2001 ; Silva et al, 2006 ; Barcoto et al, 2017 ; do Nascimento et al, 2017 ; Bizarria et al, 2018 ). Instead of being considered as a consequence of Escovopsis pathogenicity ( Currie, 2001 ; Currie et al, 2003 ; Reynolds and Currie, 2004 ; Folgarait et al, 2011 ; Varanda-Haifig et al, 2017 ), we suggest that such outcomes also integrate the fungal cultivar responses.…”
Section: Discussionmentioning
confidence: 99%
“…Trichoderma species have been reported as potential biological control agents against leafcutter ants, due to its antagonism towards the mutualistic fungal partner [28,30]. In addition, Trichoderma is a well-known biological control agent of several plant pathogens [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the real impact and modes of action of the invading filamentous fungi against the ant cultivar are still elusive. Considering fungus-fungus interactions, several studies showed growth inhibition of L. gongylophorus by filamentous fungi [14,[28][29][30][31][32]. Such interactions can be understood as interference and/or exploitation competition [33].…”
Section: Introductionmentioning
confidence: 99%